Involvement of Families as Owners of Cultural Heritage Improving Religious Tourism in Banda Aceh: Perspective of Maslahah Theory - Mukhtar, Marduati; Haniffa, Mohamed Ali; Paidi, Zulhilmi bin; Thaib, Mawardi M. (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
The increase in the tourism sector, particularly religious and cultural tourism to Indonesia, especially Aceh, can contribute to the increasing number of visits. This study aims to discuss families’ involvement in managing cultural heritage in Banda Aceh. The research method is phenomenological qualitative research, analyzed using maslahah theory. Data collection techniques used are interviews, observation, and document analysis. The results indicate that some cultural heritages in Banda Aceh have economic, historical, and religious value. One of the preferred tourist destinations is the Tomb of Sheikh Abdurrauf, which is visited by many domestic and foreign tourists. Apart from that, the involvement of families or heirs as managers of cultural heritage will provide maslahah value, or benefits, for the heirs, country, tourists, and the public in general. Among others, the benefits for the heirs are both economically and responsibly as an inheritance from their ancestors. For the country, the cultural sites will be maintained and remain sustainable, thus bringing in foreign exchange. Meanwhile, for the tourists and the public, the benefit will meet their tourism, spiritual and economic needs. Another addition is that the site is historical evidence of the great scholar who played a role in the spread of Islam in the archipelago and the Southeast Asian peninsula. Therefore, the preservation of cultural heritage involving the heirs is paramount in the context of maslahah.